Compound Parabolic Concentrator Design: Assessment of Performance Enhancement for Building-Integrated Photovoltaic Systems - Mc Cormack, Sarah; Saers, Sander; Ortega, Anita; Chandra, Subhash (My University, 2021)
Improvement of state-of-the-art sustainable energy technology is required to accelerate the essential global transition away from fossil fuel energy sources. One potential method to increase the energy output of building integrated photovoltaics (BIPV) is achieved by using parabolic reflectors, commonly known as compound parabolic concentrators (CPC). These curved mirrors allow incoming sunlight to be focused onto adjacent solar panels, thereby increasing irradiance. Although the concentrating effects of CPCs have been demonstrated in multiple studies, large scale adoption of BIPV-CPC systems has been held back due to variability in performance and added financial cost. This study aims to assess the technical performance of BIPV-CPC systems through comparison of varying designs characteristics and environmental conditions using simulation models for two locations Dublin, Ireland and Ferrara, Italy.
World Renewable Energy Congress
PUBLISHED
Keywords: Photovoltaics; Compound parabolic concentrator; Building integration